How Entrepreneurship Education and Entrepreneurial Skills Shape Entrepreneurial Motivation Through Self-Efficacy? - Subroto, Desty Endrawati; Widodo, Aris; Karapa, Abi Matius (Indonesian Journal of Business and Entrepreneurship Research, 2025)
This study examines the direct and indirect effects of entrepreneurship education and entrepreneurial skills on entrepreneurial motivation through self-efficacy in the higher education context. The study was motivated by the importance of entrepreneurship development as a strategic response to employment challenges and the need to encourage students to become job creators. A quantitative descriptive explanatory approach was employed to analyze the relationships among the variables. The population consisted of 600 students, and 102 respondents were selected using proportional random sampling. Data were collected through a structured questionnaire and analyzed to assess the direct and indirect relationships between entrepreneurship education, entrepreneurial skills, self-efficacy, and entrepreneurial motivation. The findings indicate that entrepreneurship education and entrepreneurial skills have significant effects on self-efficacy and entrepreneurial motivation. Self-efficacy also has a significant positive effect on entrepreneurial motivation and plays an important mediating role in explaining how entrepreneurship education and entrepreneurial skills strengthen students’ entrepreneurial motivation. These results suggest that entrepreneurship learning should not only emphasize conceptual understanding but also develop practical skills and confidence in managing, marketing, evaluating, and sustaining business activities. The study highlights the importance of strengthening entrepreneurship-oriented education to foster stronger entrepreneurial motivation among students.